Hubungan Ketidaksesuaian Jurusan Dengan Stres Mahasiswa Dalam Menjalankan Kegiatan Perkuliahan : The Relationship between Department of Disappointment and Student Stress in Carrying out Lecture Activities - Putri Wahyu Wulandari; Sancka Stella; Indri Sarwilly (Jurnal Interprofesi Kesehatan Indonesia, 2022)
ntroduction: Incompatibility with majors with student stress in carrying out lecture activities is closely related and affects student stress. Objectives: This study was to determine the relationship between major incompatibility with student stress in the line of lecture activities at STIKIM. Method: The research design used was analytic correlation with a cross sectional correlation or cross sectional approach. The population in this study was the sixth semester STIKIM students. The sampling technique used Google from as many as 75 respondents. The data used is through the distribution of questionnaires through the media google from. Result: The results of statistical tests of discrepancies with majors and student stress obtained the value of Asymp, Sig. (2-tailed) 0.023 (p < 0.05). Conclusion: There is a relationship between the variable of discrepancy with student stress in carrying out lectures at STIKIM.